Cytotoxicity of the Sesquiterpene Lactone Spiciformin and Its Acetyl Derivative against the Human Leukemia Cell Lines U-937 and HL-60 - Saavedra, Ester (Int J Mol Sci, 2020)
Spiciformin (1) is a sesquiterpene lactone with a germacrane skeleton that is found in two Tanacetum species endemic to the Canary Islands. In this study, the cytotoxicities of 1 and its acetyl derivative (2) were evaluated against human tumor cells. These sesquiterpene lactones were cytotoxic against human acute myeloid leukemia (U-937 and HL-60) cells, even in cells over-expressing the pro-survival protein Bcl-2, but melanoma (SK-MEL-1) and human mononuclear cells isolated from blood of healthy donors were more resistant. Both compounds are apoptotic inducers in human leukemia U-937 cells. Cell death was mediated by the processing and activation of initiator and effector caspases and the cleavage of poly(ADP-ribose) polymerase, and it was blocked by a broad-spectrum caspase inhibitor and (in the case of sesquiterpene lactone 2) by the selective caspase-3/7, -8, and -9 inhibitors. In addition, certainly in the case of compound 2, this was found to be associated with a decrease in mitochondrial membrane potential, downregulation of the anti-apoptotic protein Bcl-2, activation of the mitogen-activated protein kinases signaling pathway, and generation of reactive oxygen species. It will, therefore, be relevant to continue characterization of this class of compounds.